Improved greenhouse cucumber production under deficit water and fertilization in Northern China - Al Mamun Hossain, Shaikh Abdullah; Wang, Lixue; Liu, Haisheng (International Journal of Agricultural and Biological Engineering, 2018)
The objective of this study was to investigate the effects of different water and fertilizer applications on biomass, yield and fruit physical quality of greenhouse cucumber under drip irrigation. The experiment was conducted at Water Conservancy Research Institute, Shenbei District, Shenyang, Northern China during February-July, 2016. Nine treatments were used in randomized block design consisted of three levels of water field capacity (FC) and urea-potash (N-K) fertilizer combinations: W1 (65% of FC), W2 (75% of FC), W3 (85% of FC) and N1-K1 (285-305 kg/hm2), N2-K2 (420-435 kg/hm2), N3-K3 (530-565 kg/hm2). Local farmers’ conventional application of water (100%) and fertilizer (NPK) was considered as check (CK) for comparison. Data obtained was analyzed (ANOVA) to check the significant effect of treatments. The results revealed that, treatment W3N2K1 obtained highest cucumber yield of 129.99 t/hm2, while W1N1K1 recorded the lowest yield (113.29 t/hm2), in which total amount of seasonal water applied ranges from 85.3 mm to 172.36 mm. The highest yield was obtained 0.5% greater than the CK yield (129.35 t/hm2). The water and fertilizer application was significantly (p<0.001) influenced on cucumber yield. Moreover, the influence of water application was significantly (0.01<p<0.05) on both green and dry biomass accumulation except green leaf weight and fruit physical quality. It was also revealed that, the highest green biomass accumulation (572.4 g/plant) and fruit diameter (27.92 mm) with treatment W3N2K1 have significant influence on improved yield. In conclusion, the improved cucumber yield indicated 15% deficit water tolerance, in which average seasonal yield response factor (Ky) was calculated as 0.22. Therefore, the treatment W3N2K1 could successfully be used to minimize water and fertilizer application for improving greenhouse cucumber yield.Keywords: cucumber, drip irrigation, fertilizer, greenhouse, yieldDOI: 10.25165/j.ijabe.20181104.3566Citation: Mamun Hossain S A, Wang L X, Liu H S. Improved greenhouse cucumber production under deficit water and fertilization in Northern China. Int J Agric & Biol Eng, 2018; 11(4): 58-64.